Gene novelty and gene family expansion in the early evolution of Lepidoptera - Hoile, AE; Holland, PWH; Mulhair, PO (BioMed Central, 2025)
Background Almost 10% of all known animal species belong to Lepidoptera: moths and butterflies. To understand how this incredible diversity evolved we assess the role of gene gain in driving early lepidopteran evolution. Here, we compared the complete genomes of 115 insect species, including 99 Lepidoptera, to search for novel genes coincident with the emergence of Lepidoptera. Results We find 217 orthogroups or gene families which emerged on the branch leading to Lepidoptera; of these 177 likely arose by gene duplication followed by extensive sequence divergence, 2 are candidates for origin by horizontal gene transfer, and 38 have no known homology outside of Lepidoptera and possibly arose via de novo gene genesis. We focus on two new gene families that are conserved across all lepidopteran species and underwent extensive duplication, suggesting important roles in lepidopteran biology. One encodes a family of sugar and ion transporter molecules, potentially involved in the evolution of diverse feeding behaviours in early Lepidoptera. The second encodes a family of unusual propeller-shaped proteins that likely originated by horizontal gene transfer from Spiroplasma bacteria; we name these the Lepidoptera propellin genes. Conclusion We provide the first insights into the role of genetic novelty in the early evolution of Lepidoptera. This gives new insight into the rate of gene gain during the evolution of the order as well as providing context on the likely mechanisms of origin. We describe examples of new genes which were retained and duplicated further in all lepidopteran species, suggesting their importance in Lepidoptera evolution.